METHODS OF TEACHING THE GERMAN LANGUAGE. ANALYSIS OF MODERN PEDAGOGICAL APPROACHES (International journal of medical sciences, 2026)
This article examines contemporary methods of teaching German as a foreign language, highlighting their theoretical foundations and practical significance in modern education. Particular attention is given to communicative and competence-based approaches, interactive teaching strategies, and the integration of digital technologies into the learning process. The study analyzes how effective methodology contributes to the development of students’ linguistic, sociolinguistic, and intercultural competencies. It also discusses the transition from traditional grammar-oriented instruction toward learner-centered and practice-oriented models. The findings suggest that combining communicative methods with innovative educational technologies enhances students’ motivation, autonomy, and overall language proficiency.